Rhizoma coptidis inhibits LPS-induced MCP-1/CCL2 production in murine macrophages via an AP-1 and NFk B-dependent pathway - Remppis, Bjoern-Andrew; Bea, Florian; Greten, Henry Johannes; Buttler, Annette; Wang, Hongjie; Zhou, Qianxing; Preusch, Michael R.; Enk, Ronny; Ehehalt, Robert; Katus, Hugo; Blessing, Erwin (Mediators of inflammation, 2010)
Introduction. The Chinese extract Rhizoma coptidis is well known for its anti-inflammatory, antioxidative, antiviral, and antimicrobial activity. The exact mechanisms of action are not fully understood. Methods. We examined the effect of the extract and its main compound, berberine, on LPS-induced inflammatory activity in a murine macrophage cell line. RAW 264.7 cells were stimulated with LPS and incubated with either Rhizoma coptidis extract or berberine. Activation of AP-1 and NF B was analyzed in nuclear extracts, secretion of MCP-1/CCL2 was measured in supernatants. Results. Incubation with Rhizoma coptidis and berberine strongly inhibited LPS-induced monocyte chemoattractant protein (MCP)-1 production in RAW cells. Activation of the transcription factors AP-1 and NF B was inhibited by Rhizoma coptidis in a dose- and time-dependent fashion. Conclusions. Rhizoma coptidis extract inhibits LPS-induced MCP-1/CCL2 production in vitro via an AP-1 and NF B-dependent pathway. Anti-inflammatory action of the extract is mediated mainly by its alkaloid compound berberine.
Gesehen am 12.05.2023